Late Pleistocene-Dated Divergence Between South Hemisphere Populations of the Non-Conventional Yeast L. Cidri - Cubillos-Riffo, F; Villarreal-Diaz, P; Pena-Echeverria, T (John Wiley and Sons Inc, 2022)
Most organisms belonging to the Saccharomycotina subphylum have high genetic diversity and a vast repertoire of metabolisms and lifestyles. Lachancea cidri is an ideal yeast model for exploring the interplay between genetics, ecological function and evolution. Lachancea cidri diverged from the Saccharomyces lineage before the whole-genome duplication and is distributed across the South Hemisphere, displaying an important ecological success. We applied phylogenomics to investigate the genetic variation of L. cidri isolates obtained from Australia and South America. Our approach revealed the presence of two main lineages according to their geographic distribution (Aus and SoAm). Estimation of the divergence time suggests that SoAm and Aus lineages diverged near the last glacial maximum event during the Pleistocene (64-8 KYA). Interestingly, we found that the French reference strain is closely related to the Australian strains, with a recent divergence (405-51 YA), likely associated to human movements. Additionally, we identified different lineages within the South American population, revealing that Patagonia contains a similar genetic diversity comparable to that of other lineages in S. cerevisiae. These findings support the idea of a Pleistocene-dated divergence between South Hemisphere lineages, where the Nothofagus and Araucaria ecological niches likely favoured the extensive distribution of L. cidri in Patagonia. © 2022 Society for Applied Microbiology and John Wiley & Sons Ltd.